2004
DOI: 10.1051/forest:2004018
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the intra-ring wood density assessed by X-ray densitometry and optical anatomical measurements in conifers. Consequences for the cell wall apparent density determination

Abstract: -The objective of this work is to compare anatomical measurements to wood density variations within annual rings of three major softwood species, Norway spruce, Scots Pine and Silver Fir. The six selected annual rings were sampled within a database of thousand microdensitometric profiles measured on wood samples collected in Finland and France. Each of the six studied annual rings represents one average profile of wood density for a given age class and age ring width. The dimensions of the tracheids are perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 17 publications
4
57
1
11
Order By: Relevance
“…Decoux et al (2004) have reported that WD exhibits maximum variance within individual annual rings, ranging from ca. 300 to 1000 kg m -3 .…”
Section: Intra-annual Variation In Wood Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Decoux et al (2004) have reported that WD exhibits maximum variance within individual annual rings, ranging from ca. 300 to 1000 kg m -3 .…”
Section: Intra-annual Variation In Wood Densitymentioning
confidence: 99%
“…300 kg m -3 in earlywood to ca. 1000 kg m -3 in latewood (Olesen 1982, Mäkinen et al 2002b, Decoux et al 2004). The increase in WD from early-to latewood is mainly due to anatomical changes in tracheids (Kellogg andWangaard 1969, Skaar 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This variation is produced because of the differences in tracheid formation of early and latewood in softwood species (Decoux et al, 2004). In contrast with the hardwoods, the variation depends on the amount or proportion of different cell types and spatial arrangements (Guilley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A densidade da madeira das espécies florestais é, reconhecidamente, a propriedade mais analisada nos laboratórios de tecnologia da madeira e de produtos florestais, pelas relações com as demais propriedades e utilização da madeira (Decoux et al, 2004), bem como na determinação da biomassa e incorporação do carbono pelo tronco das árvores e na caracterização dos anéis de crescimento (Guilley et al, 2004e Sckinker et al, 2003.…”
Section: A Densitometria De Raios X Na Determinação Da Densidade Da Munclassified
“…As variações da densidade da madeira de um anel de crescimento ou de uma seção transversal de amostra de madeira têm forte influência na qualidade de madeira (Echols, 1973) sendo mais importantes quando associadas às características anatômicas (Decoux et al, 2004).…”
Section: Variações No Perfil Da Densidade Da Madeira Por Densitometriunclassified